Using participatory video to explore teachers’ lived experiences - Olivier, Tilla; De Lange, Naydene; Wood, Lesley (Faculty of Education, University of the Free State, 2010)
Teachers who work in economically and socially disadvantaged environments have first-hand knowledge of the challenges that can impede teaching and learning, yet their voices are often ignored when researchers and policy-makers attempt to address such issues. In this article we describe how we attempted to make teacher voices audible via an intervention based on participatory visual methodology. A two-day participatory research-as-intervention workshop enabled twelve teachers from economically and socially disadvantaged township schools to produce videos that examined some challenges applicable to their praxis. The process of producing the participatory video offered the teachers the opportunity to learn more about themselves and their educational contexts, and to position themselves as “teachers who care”, as they collectively identified pertinent issues affecting their practice, decided on how to represent those issues visually and how to further use the finished product as a tool for teaching and/or community engagement.
Keywords: Participatory visual methodologies; Research as intervention; Participatory video; Agency; Pastoral role